EVIDENCE FOR THE LEADING ROLE OF TEMPERATURE VARIATIONS RELATIVE TO GREENHOUSE GAS CONCENTRATION VARIATIONS IN THE VOSTOK ICE CORE RECORD - Vakulenko N.V.; Kotlyakov V.M.; Monin A.S.; Sonechkin D.M. (My University, 2004)
Dependence of concentrations of green-house gases in atmosphere on long-term variations of temperature has been considered. It is assumed that technogeneous factor plays the main role in the global warming. However, that there are data which do not agree with this. The data were obtained by means of 'Vostok' station. It has been shown that increase in carbon dioxide lags behind. Mathematical model of the concentration variation has been developed with the use of integral equations. Periods of warming have been calculated with the use of the model. Results of the calculations have shown that the concentrations of the greenhouse gases do not play the main role.